Infant lung function predicts asthma persistence and remission in young adults - Owens, L.; Laing, I.; Zhang, Guicheng; Le Souëf, P. (Wiley-Blackwell Publishing Asia, 2017)
Background and objective: Asthma in adults is associated with a persistent reduction in lung function from childhood, but this link has not been assessed back to infancy. Reduced infant lung function (ILF), a measure of antenatal and infant lung growth, is associated with asthma into adolescence. Our aim was to assess whether this link persists into adulthood and whether ILF can predict the remission of asthma symptoms in young adults. Methods: The study cohort was an unselected full-term birth cohort of 253 subjects enrolled antenatally with lung function assessments at 1, 6 and 12months (maximum expiratory flow at functional residual capacity, V'maxFRC), and 6, 11, 18 and 24years (spirometry) of age. Results: Infants with V'maxFRC in the lowest quartile at 1month had an OR of 5.1 (95% CI: 2-13, P=0.001) for asthma at 24years. Subjects with asthma at 24years had a mean V'maxFRC at 1 month of 69% predicted (95% CI: 48-90%) versus 110% (95% CI: 101-119%) in non-asthmatic patients (P=0.001). Subjects with current versus resolved asthma symptoms at 24years had a mean V'maxFRC at 1month of 69% predicted (95% CI: 53-84%) versus 105% (88-123%), respectively (P=0.003). Subjects with current asthma at 24years had persistently lower lung function from infancy with a mean reduction of 16.2% (95% CI: 8.1-24.3%, P<0.0001). Conclusion: Reduced lung function in early infancy is predictive of persistent asthma in young adults and a persistent reduction in lung function, suggesting abnormal lung development and growth in utero or very early in life.